(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Micromorphological characters of achenes in seven taxa of Turkish Achillea L. (Asteraceae) were investigated using stereomicroscope and scanning electron microscope (SEM). Some morphological descriptions of achenes were given for each species. A.biserrata Bieb. has the biggest (0.69±0.092 x 2.01±0.252 mm) and A. grandiflora Friv. has the smallest (0.30±0.018 x 1.12±0.058 mm) achenes. The achenes are oblong-lanceolate in A.biserrata and A. teretifolia Willd. and they are oblong in the remaining taxa. In surface sculpturing, the ornamentation and slime cell distribution varied among the taxa. However, A. biebersteinii Afan. has distinct slime cells forming groups scattered over the achene surface. Mature achenes are ribbed and glabrous in all studied taxa. A. biserrata has distinct carpopodium structure. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19253 Bangladesh J. Plant Taxon. 21(1): 19-25, 2014 (June)